(untitled) (Balthazar, 2025)
Much of contemporary animal ethics can be read as a reaction to its rationalistic roots, trying to correct for an epistemically impoverished picture of moral cognition. This “affective turn” in animal ethics which seeks to take seriously the role of affective cognition in moral deliberation has been very fruitful but it has also resulted in a tendency to take affective intuitions as evidence against alienating, demanding or repulsive conclusions from traditional, principle-based universalist ethics. I argue that this is a mistake. Rather than elevating our affects to the position of evidence, taking their role in moral cognition seriously should actually make us more scrupulous in their use, not less. If moral cognition inescapably involves the use of feelings and emotions, I argue, then we must be especially careful to keep our feelings and emotions free from biases and fallacies. This will involve more intense alienation from and reevaluation of our affective intuition, not less.